Antibacterial Studies of Copper(I) Complexes with Benzoylthiourea Derivatives - Zhao, Meng-Meng; Dong, Xiu-Yan; Yang, Yu-Hua; Li, Gang; Zhang, Yu-Jie; Yang, Xiao-Qin (Asian Journal of Chemistry, 2013)
Four copper(I) complexes of bisbenzoylthiourea derivatives have been synthesized and characterized by elemental analyses as well as IR spectroscopy and TG-DTA analyses. Antibacterial activity assay exhibited MIC50 values of these compounds comparable to standard drugs for both gram-positive and gram-negative bacteria, some of them showed great antibacterial activity.